2017
DOI: 10.1124/jpet.117.241141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute and Chronic Treatments with Dopamine D2 and D3 Receptor Ligands on Cocaine versus Food Choice in Rats

Abstract: Dopamine D receptor ligands are potential medications for psychostimulant addiction. Medication assessment may benefit from preclinical studies that evaluate chronic medication effects on choice between an abused drug and an alternative, nondrug reinforcer. This study compared acute and chronic effects of dopamine D- and D-preferring ligands on choice between intravenous cocaine and palatable food in rats. Under baseline conditions, cocaine maintained dose-dependent increases in cocaine choice and reciprocal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…The M 1 /M 4 receptor-preferring agonist xanomeline reduced cocaine taking in rats given access to choose between cocaine or a palatable food reinforcer [23]. Unlike effects of dopamine receptor ligands in the same assay [24,25], the effects of M 1 /M 4 stimulation grew larger during subchronic dosing, and subsisted briefly after ended treatment [23]. In mice, M 1 /M 4 stimulation facilitated extinction of cocaine seeking and prevented reinstatement of cocaine seeking when administered during extinction or between cocaine exposure and extinction [26].…”
Section: Introductionmentioning
confidence: 93%
“…The M 1 /M 4 receptor-preferring agonist xanomeline reduced cocaine taking in rats given access to choose between cocaine or a palatable food reinforcer [23]. Unlike effects of dopamine receptor ligands in the same assay [24,25], the effects of M 1 /M 4 stimulation grew larger during subchronic dosing, and subsisted briefly after ended treatment [23]. In mice, M 1 /M 4 stimulation facilitated extinction of cocaine seeking and prevented reinstatement of cocaine seeking when administered during extinction or between cocaine exposure and extinction [26].…”
Section: Introductionmentioning
confidence: 93%
“…In addition, overexpression of let-7d is negatively correlated with the expression of DRD3 in the hippocampus of mice (Bahi and Dreyer, 2018). The activity of the DRD3 is controversy in the context of food intake, but some evidences associate it with eating disorders and decreased food intake (Thomsen et al, 2017;González et al, 2019). The expression of DAT, the major controller of dopamine levels in the synaptic clefts, is post-transcriptionally regulated on cell culture of dopaminergic neurons by miR-137 and miR-491 (Jia et al, 2016).…”
Section: Dopamine: Role On Feeding Behavior Influences Of Els and Mmentioning
confidence: 99%
“…As thoroughly reviewed by Sokoloff and Le Foll [9], D3R drugs reduce cocaine-motivated behaviors on high-but not low-effort schedules of reinforcement. Dopamine D3R partial agonists and antagonists are generally ineffective in altering cocaine intake on low fixed ratio schedules requiring 5 or fewer responses [10][11][12][13][14]. Similarly, we have found that cocaine intake on a low-effort variable interval (VI) 60 s schedule of reinforcement is only affected at doses of D3R partial agonists and antagonists that also affect sucrose reinforcement and cocaine-induced locomotor activity [11].…”
Section: Introductionmentioning
confidence: 76%